Solidifying what is known about calibration artefacts and the development of an educational tool to assist in the teaching of interferometric imaging - Jackson, Jason Peter (Stellenbosch : Stellenbosch University, 2023)
Thesis (MSc)--Stellenbosch University, 2023.